2016
DOI: 10.1158/1078-0432.ccr-16-0423
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal Administration of Fc-Fused IL7 Suppresses the Cervicovaginal Tumor by Recruiting HPV DNA Vaccine-Induced CD8 T Cells

Abstract: Purpose: The induction of tissue-localized virus-specific CD8 T-cell response is essential for the development of an effective therapeutic vaccine against genital diseases, such as cervical cancer and genital herpes. Here, we aimed to elucidate the immunologic role of IL7 in the induction of mucosal cellular immunity.Experimental Design: IL7 was engineered through Fc fusion to enhance mucosal delivery across the genital epithelial barrier. The immunomodulatory role of IL7 was evaluated by monitoring the kineti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…A previous study suggested that local immune response along with systemic immune response result in histologic regression (22). Other studies also showed that a therapeutic HPV DNA vaccination in combination with intravaginal administration of immune modulator recruits antigen-specific CD8 þ T cells to the genital tract, leading to tumor control in a mouse cervical cancer model (23,24). Thus, further study to investigate a role of local and systemic immunity in efficacy of therapeutic vaccine in CIN3 patients may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that local immune response along with systemic immune response result in histologic regression (22). Other studies also showed that a therapeutic HPV DNA vaccination in combination with intravaginal administration of immune modulator recruits antigen-specific CD8 þ T cells to the genital tract, leading to tumor control in a mouse cervical cancer model (23,24). Thus, further study to investigate a role of local and systemic immunity in efficacy of therapeutic vaccine in CIN3 patients may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human IL-7-hyFc is an engineered protein that has long bioavailability. 21,22 To investigate the systemic pharmacodynamic effects of rhIL-7-hyFc treatment, we subcutaneously (s.c.) administered a single dose of rhIL-7-hyFc and examined the immune compartments in the peripheral blood. rhIL-7-hyFc significantly increased CD3e + T cells peaked at day 7, and the increment was remained up to day 12 ( Figure 1a).…”
Section: Administration Of Rhil-7-hyfc Increases Cd8 + T Cells and Sumentioning
confidence: 99%
“…Hence, we developed a hybrid Fc‐fused long‐acting recombinant human IL‐7 (rhIL‐7‐hyFc, efineptakin‐alfa‐7 TM ) with no cytotoxicity on target cells and a long half‐life in vivo . Single topical treatment with rhIL‐7‐hyFc after administration of a DNA vaccine, which encodes tumor antigen, elicits antitumor responses by expanding populations of vaccine‐induced tumor‐specific CD8 + T cells 21 . rhIL‐7‐hyFc is thus potentially applicable as a novel cytokine‐based drug for cancer immunotherapy; however, the mechanisms underlying rhIL‐7‐hyFc‐mediated modulation of immune cells in the TME remain undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…104 Administration of Fc-fused IL7 could also play a role in modulating vaccines therapy through a CD8+ T cell response. 105 Various therapeutic vaccines are being developed, including DNA, RNA and peptide vaccines. All of these vaccines types exerted antitumor effects through activating the T cell response, especially CD8+ cells.…”
Section: Therapeutic Vaccines and Cytokinesmentioning
confidence: 99%